Taqdīm dan Ta'khir dalam Al-Qur'an (Pendekatan Qawāid al-Lughah al-‘Arabiy ah) - Abd. Karim Hafid (Al-Jami'ah Research Centre, 2001)
There are many secrets and wonders in the precedence and postponement in holy Qur'an previewed from both linguistic structure and grammatical point of view. One of these secrets may lay in the utilizing a single word for different linguistic purposes in different parts of the speech in which a speaker may have certain different meanings. The following article is trying to show these sorts of Precedence and Postponement, categorizing them into two kinds:1- Precedence and postponement as previewed in a linguistic point of view, considering the use of words in phrases or verses depending on standard grammars stated by the linguists.2- Precedence and postponement as previewed in the terminologist point of view, considering in the holy Qur'an.The first type discusses the principle of faith and literature that has the purpose of precedence and postponement for specialization as it leads to the principle of unity of almighty God. The research involves the precedence and postponement which is found (from linguistic point of view) in the holly verses of Qur'an, such as, preceding the reference on the reference to or vice versa. The precedence and postponement have an influence (on the terminology point of view) on understanding of the holly Qur’an, especially for worshipping and lows. In worshipping, the precedence and postponement, may concern the arrangement of certain deeds like performing the ablutions (wudlu) before praying than praying. For laws or rules, it precede the male's name before the female's, and also, preceding the more than the less; such as preceding the man thief on the woman thief, for many of those could be man, and preceding woman on man in adultery.